Копні суди в державно-правовій системі Гетьманщини (1648 - 1783 pp.) - Бедрій, М.М. (Часопис Київського університету права, 2009)
В данной статье определяется правовое положение копных судов в судебной системе Гетманщины. Представлен анализ их взаимодействия с другими органами власти козацкого государства. Автор сравнивает правовой статус судов в XVII и XVIII веках, анализирует изменения, которые в нем происходили, а также их причины и последствия. In this article legal position of community courts is determined in the judicial system of Get’manschina. The analysis of their co-operating with other bodies of power of the kosaks state is presented. An author compares legal status of community courts in XVII and XVIII ages, analyses changes, which took a place in him, and also their reasons and consequences.